Evaluation of the extent and pattern of use of herbal (2014)
Purpose: To evaluate the extent and pattern of use of herbal bitters among students. Methods: This was a cross-sectional study where pre-tested structured questionnaires were administered to 1000 students. The questionnaire elicited information on the extent and pattern of use, self-reported indications, side effects experienced and possible drugs that were concomitantly coadministered with herbal bitters. Pearson Chi square, Fisher exact test and Relative risk ratio were used to detect association between gender and self-reported indications and side effects experienced with herbal bitters at a level of significance of p < 0.05. Results: The response rate and extent of use were 96 % and 40.9 % respectively. Herbal bitters were used for claims such as cleansers 88 (40.2 %), anti-infectives 48 (21.1 %), for rejuvenation 32 (14.0 %), and for weight loss 14 (6.1 %). Self-reported side effects included dizziness 49 (22.0 %), loss of taste 46 (20.6 %) and nausea and vomiting 22 (9.7 %). Herbal bitters were also co-administered with antimalarials 22 (6.3 %); analgesics 16 (4.5 %) and herbal supplements 13 (3.7 %). Reports of students using two different types of herbal bitter concurrently 15 (3.9 %) were also garnered. Male students experienced more side effects than females (p < 0.05). Conclusion: The co-administration of herbal bitters with allopathic medicines and the use of more than one herbal bitter at a time reported in this study can be addressed by the appropriate health authorities through proper educational programme.